Hubungan Internal Monitoring Mechanism dan Accounting Conservatism dengan Analyst Coverage Sebagai Variabel Moderasi - Triana Retnosari; Niluh Putu Dian Rosalina Handayani Narsa (Wahana Riset Akuntansi, 2022)
This study aims to determine the role of analyst coverage as a moderating variable in the relationship between internal monitoring mechanisms and the level of application of accounting conservatism. This research was conducted on a 990 sample of non-financial companies during the 2014-2018 period which was obtained from the official website of the IDX and related companies. Data processing uses the Stata14 application with moderated regression analysis (MRA) testing. The results of this study indicate that two components of internal monitoring mechanisms, namely board size and board independent have a negative relationship with accounting conservatism, while audit committee independent do not have a relationship with accounting conservatism. Furthermore, analyst coverage is proven to be quasi-moderation in the relationship between board size and audit committee independent with the level of accounting conservatism implementation. The relationship model between board independent and accounting conservatism cannot show the moderating role of analyst coverage, and only being an additional independent variable.Keywords: accounting conservatism, analyst coverage, audit committee independent, board independent, board size, monitoring.